Single Domain Antibodies Targeting Receptor Binding Pockets of NadA Restrain Adhesion of Neisseria meningitidis to Human Brain Microvascular Endothelial Cells - Kulkarni, Amod; Mochnáčová, Evelína; Majerova, Petra; Čurlík, Ján; Bhide, Katarína; Mertinková, Patrícia; Bhide, Mangesh (Frontiers in Molecular Biosciences, 2020)
Neisseria adhesin A (NadA), one of the surface adhesins of Neisseria meningitidis (NM), interacts with several cell types including human brain microvascular endothelial cells (hBMECs) and play important role in the pathogenesis. Receptor binding pockets of NadA are localized on the globular head domain (A33 to K69) and the first coiled-coil domain (L121 to K158). Here, the phage display was used to develop a variable heavy chain domain (VHH) that can block receptor binding sites of recombinant NadA (rec-NadA). A phage library displaying VHH was panned against synthetic peptides (NadA-gdA33-K69 or NadA-ccL121-K158), gene encoding VHH was amplified from bound phages and re-cloned in the expression vector, and the soluble VHHs containing disulfide bonds were overexpressed in the SHuffle E. coli. From the repertoire of 96 clones, two VHHs (VHHF3 - binding NadA-gdA33-K69 and VHHG9 - binding NadA-ccL121-K158) were finally selected as they abrogated the interaction between rec-NadA and the cell receptor. Preincubation of NM with VHHF3 and VHHG9 significantly reduced the adhesion of NM on hBMECs in situ and hindered the traversal of NM across the in-vitro BBB model. The work presents a phage display pipeline with a single-round of panning to select receptor blocking VHHs. It also demonstrates the production of soluble and functional VHHs, which blocked the interaction between NadA and its receptor, decreased adhesion of NM on hBMECs, and reduced translocation of NM across BBB in-vitro. The selected NadA blocking VHHs could be promising molecules for therapeutic translation.